LEARNING MEDIA TRAINING AND ASSISTANCE FOR BUDDHIST SUNDAY SCHOOL MANAGEMENT IN WONOGIRI REGENCY - Novianti, Novianti; Marjianto, Marjianto; Darma, Widia; Setyaningsih, Ratna; Putro, Adi Nugroho Susanto; Wulan, Ayuning (LPPM Univ. Ibn Khaldun Bogor, 2024)
As part of implementing the Tri Dharma of Higher Education, the lecturer team in STAB Negeri Raden Wijaya Wonogiri, Central Java conducted community service activities in the form of